Novel architecture for anomalous strengthening of a particulate filled polymer matrix composite1. Issue 77 (22nd August 2015) - Reddy, Siva Kumar; Lal, Devi; Misra, Abha; Kumar, Praveen
<x xml:space="preserve">Abstract</x> We propose an architecture for dramatically enhancing the stress bearing and energy absorption capacities of a polymer based composite.